Between Tradition and Digitality: The Hybridity of Islamic Identity Among Indonesian Millennial Muslims - Wardi, Ujang (Institut Agama Islam Negeri (IAIN) Curup, 2026)
This study examines the formation of Islamic identity among Indonesian millennial Muslims amid massive digital transformation. Employing a qualitative approach supported by a survey of 670 respondents across seven major cities (September 2022–February 2023), the research analyzes identity dynamics through the frameworks of primordialism, instrumentalism, and constructivism, elaborated with Homi K. Bhabha’s concept of hybridity. Findings reveal that Islamic identity is not formed through a linear shift from tradition to digital modernity, but through simultaneous dialectical negotiation. Identity legitimacy remains rooted in family bonds (80.63%) and ascribed identity (83.92%), while engagement in digital religious discourse is lowest (57.76%). Notably, religious community interaction via digital spaces reaches 91.98%, indicating that technology functions as an additional arena of articulation rather than a source of fundamental religious values. Millennial Muslim identity is hybrid in nature—preserving traditional religio-cultural roots while reflexively adapting to the digital ecosystem through continuous social negotiation within a third space. This identity construction is relational, contextual, and cannot be understood reductionistically.